3D printing of micropatterned stamps with tunable horizontal surface properties. (16th December 2022) - Bail, Robert; Lee, Su Bin; Lee, Dong Hyun
Abstract : Resin three‐dimensional (3D) printing is potentially attractive for the rapid fabrication of micropatterning tools such as stamps, molds, masks, or substrates. Although the horizontal surface finish of a resin 3D printed part is generally considered to be very smooth, it is strongly influenced by the microscale interaction of the printer light source with the photopolymerizable resin. This study demonstrates how a glossy surface can be created on an elastic 3D printed component by extreme overexposure of the cap layer and how this can be analyzed. The average roughness ( R a ) values of the surface in the X and Y directions could be reduced by a factor of 4.5 (X) to 5.0 (Y) from initially 0.182/0.343 to 0.041/0.069 μm (X/Y), and geometric accuracy was ensured by undersizing the features in the cap layer. The practical relevance of controlling the horizontal surface properties was demonstrated using a 3D printed stamp to transfer a micropattern of light‐emitting quantum dots. The insights gained will be useful in the fabrication of 3D‐printed tools for creating high‐resolution patterns from quantum dots, semiconductors, and organometallic materials.